2011
DOI: 10.1371/journal.pgen.1002309
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type–Specific Transcriptome Analysis Reveals a Major Role for Zeb1 and miR-200b in Mouse Inner Ear Morphogenesis

Abstract: Cellular heterogeneity hinders the extraction of functionally significant results and inference of regulatory networks from wide-scale expression profiles of complex mammalian organs. The mammalian inner ear consists of the auditory and vestibular systems that are each composed of hair cells, supporting cells, neurons, mesenchymal cells, other epithelial cells, and blood vessels. We developed a novel protocol to sort auditory and vestibular tissues of newborn mouse inner ears into their major cellular componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 40 publications
(51 reference statements)
6
89
0
1
Order By: Relevance
“…Frozen sections (10-μm thick) of cochlea were prepared from Cx3cr1 GFP/+ mice as described previously (59). Sections were counterstained with Alexa Fluor 568 phalloidin (Life Technologies) diluted 1:500.…”
Section: Methodsmentioning
confidence: 99%
“…Frozen sections (10-μm thick) of cochlea were prepared from Cx3cr1 GFP/+ mice as described previously (59). Sections were counterstained with Alexa Fluor 568 phalloidin (Life Technologies) diluted 1:500.…”
Section: Methodsmentioning
confidence: 99%
“…Because the BALB QTL region is relatively small, Table 3 lists some polymorphic genes for which no cochlear role is established. Among candidates, Zeb1 is a transcription factor strongly expressed in spiral ligament (Hertzano et al 2011). One of its actions is downregulation of Cx26, a previously claimed effect of noise exposure that could depress the EP and potentially amplify injury to the organ of Corti (Nagashima et al 2010).…”
Section: Chromosome 18mentioning
confidence: 99%
“…At present, only a small proportion of the hair cell transcriptome has been identified. For example, various array- based methods (McDermott et al, 2007;Hertzano et al, 2011;Sinkkonen et al, 2011) and proteomic studies (Herget et al, 2013;Shin et al, 2013) have identified a few hundred hair cell markers. Therefore, we implemented a filter on the entire list of 3661 genes that required a Ͼ2-fold expression drop at 0 -24 h and a relative recovery by 168 h. This resulted in a list of 526 genes (some examples are shown in Table 1), within which were our 32 hair cell "sentinel" genes.…”
Section: Identifying Components Of the Hair Cell Transcriptomementioning
confidence: 99%